The Effect of Using Hand Paddles and Leg Loads on the Speed of 50 Meter Freestyle Swimming in Rejang Lebong Regency - Agus Irwanto; Sri Sumartiningsih; Ranu Baskora Aji Putra; Agung Wahyudi (Journal of Physical Education and Sports, 2022)
This study aims to evaluate the effect of using Hand Paddles and Leg Loads on the speed of 50 meter freestyle swimming in Rejang Lebong Regency. The method used is quantitative research with One Group Pre-test – Post-test Design. The research population consisted of 40 freestyle swimming athletes in Rejang Lebong Regency who were selected by purposive sampling technique. The research instrument was a 50 meter freestyle swimming test, and data analysis involved prerequisite tests, normality tests, homogeneity tests, and hypothesis testing. This study resulted in a significant difference between the use of paddles and leg load on speed in 50-meter freestyle swimming athletes and there was an increase in the effect of the relationship between achievement of freestyle swimming time before and after treatment. Freestyle swimming exercises using hand paddles and without hand paddles both give a good effect, the intensity increases for 16 meetings. mix training program with the given training pattern, in order to increase swimming speed so that it affects freestyle swimming speed.